The Role of Technology in Transforming Classroom Instruction: Teacher's perspective (Journal of Musikot Campus, 2025)
This research is focused in how technology has significantly transformed classroom education. Technology integration has transformed conventional teaching strategies and given teachers and students new options to improve educational prospects. This research has been focused on the role of technology in transforming classroom instruction from teachers' perspectives in the context of the Dailekh district. The main purpose of this research is to explore teachers' perceptions regarding the role of technology in transforming classroom instruction and find out the major challenges regarding the use of technology in classroom instructions. This article has been prepared by using the in-depth interview under the qualitative research design.  Six teachers were selected from three schools of Dailekh district by employing purposive sampling. The research highlights the advantages of use of technology in the classroom, including improved engagement, individualized instruction, access to a wealth of learning materials, and the development of crucial 21st-century skills. It also looks at potential obstacles and factors, like as infrastructure needs, teacher preparation, access of relabel internet and the technology integration. This study tries to finding the perception of teachers in classroom transformation through use of technology. All respondents were agreed in positive effects of using technology in classroom transforming